2023
DOI: 10.1021/acs.energyfuels.3c02855
|View full text |Cite
|
Sign up to set email alerts
|

Direct Investigation of Oil Recovery Mechanism by Polymer-Alternating-Gas CO2 through Micromodel Experiments

Rapheephan Laochamroonvorapongse,
Virginie Beunat,
Nicolas Pannacci
et al.

Abstract: CO2 gas is one of the most effective injectants for enhanced oil recovery (EOR). New injection technique like polymer-alternating-gas (PAG) is aimed at further improving oil recovery efficiency from conventional gas injection; however, the oil recovery mechanism and fluid interactions underlying PAG have not yet been studied at a microscopic level. This study conducts the first micromodel study to better understand the relevant mechanisms and interactions of PAG at high pressure and temperature. Traditional me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…An early attempt to mimic the realistic PAG flooding scenario involved sand-pack flooding, highlighting the effectiveness of immiscible PAG injection in extracting heavy oil where PAG injection in the tertiary mode yielded 19% oil recovery . Few coreflood experiments on sandstone cores have been conducted to demonstrate the efficacy of PAG injection, but these experiments either used model crude oil or lacked comprehensive discussion on the displacement mode of crude oil by CO 2 during PAG injection. , A micromodel study was conducted to explain the recovery mechanism of miscible PAG for 0.5 cP oil using SAV55 polymer . Furthermore, Tovar et al studied the effect of heterogeneity on miscible or immiscible displacement of oil by PAG injection in sandstone core, and their findings indicated that a certain level of heterogeneity is necessary for PAG injection to yield beneficial results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early attempt to mimic the realistic PAG flooding scenario involved sand-pack flooding, highlighting the effectiveness of immiscible PAG injection in extracting heavy oil where PAG injection in the tertiary mode yielded 19% oil recovery . Few coreflood experiments on sandstone cores have been conducted to demonstrate the efficacy of PAG injection, but these experiments either used model crude oil or lacked comprehensive discussion on the displacement mode of crude oil by CO 2 during PAG injection. , A micromodel study was conducted to explain the recovery mechanism of miscible PAG for 0.5 cP oil using SAV55 polymer . Furthermore, Tovar et al studied the effect of heterogeneity on miscible or immiscible displacement of oil by PAG injection in sandstone core, and their findings indicated that a certain level of heterogeneity is necessary for PAG injection to yield beneficial results.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 A micromodel study was conducted to explain the recovery mechanism of miscible PAG for 0.5 cP oil using SAV55 polymer. 35 Furthermore, Tovar et al 36 studied the effect of heterogeneity on miscible or immiscible displacement of oil by PAG injection in sandstone core, and their findings indicated that a certain level of heterogeneity is necessary for PAG injection to yield beneficial results. It has been observed that most of the studies focused on analyzing individual parameters to explain the additional recovery achieved through PAG injection, without fully integrating the mechanisms or optimizing various parameters such as MMP, IFT reduction, viscosity reduction, CO 2 solubility and crude oil swelling factor, and injection rate of fluids.…”
Section: Introductionmentioning
confidence: 99%
“…The implementation of CO 2 – EOR can be done under several schemes, including the injection of miscible/immiscible CO 2 , water alternating CO 2 gas injection (WAG CO 2 ), polymer alternating gas CO 2 (PAG), simultaneous water CO 2 gas injection, foam assisted CO 2 , low salinity water–surfactant–CO 2 , and hybrid schemes with surfactant polymer (SP). Most CO 2 – EOR processes are commonly confronted to satisfy two objectives consisting of maximizing ORF and minimizing the production of CO 2 (this latter means the increase in the storage performance). However, it is worth mentioning that many published studies and experimental tests demonstrated the superiority of the miscible type (single–phase flow) of CO 2 – EOR processes in reaching higher ORF compared to the immiscible type (two–phase flow). , The suitable design of a CO 2 – EOR process depends greatly on the so-called minimum miscibility pressure (MMP) since this parameter allows the determination of the injection type, i.e., miscible or immiscible. MMP represents the cutoff pressure at reservoir temperature (T R ) above which miscibility between the reservoir fluid and the injected gas occurs after multiple contacts. …”
Section: Introductionmentioning
confidence: 99%